The shareholder wealth effects of an executive joining another company's board - Byrd, J.; Martin, A.; Rath, Subhrendu (School of Economics and Finance, Curtin Business School, 2008)
Using a sample of 134 announcements of an executive joining the board of another company from 1985 through 1997, we find a negative announcement date stock response of about one-half of one percent for the home firm. Our initial regression analysis shows that the prior performance of the home firm, how close the executive is to retirement, and the number of other boards the executive already sits on, help explain the cross-sectional variation in the announcement date stock returns. The stock price response we report is larger (more negative) than that found by Rosenstein and Wyatt (1994) during an earlier sample period. We attribute the difference in our findings to investors being much more attuned to corporate governance issues during our sample period.